Isotopic Radiolabeling of Crizotinib with Fluorine-18 for In Vivo Pet Imaging - Malvika Sardana; Louise Breuil; Sébastien Goutal; Maud Goislard; Mikhail Kondrashov; Etienne Marchal; Florent L. Besson; Christophe Dugave; Gail Wrigley; Anna C. Jonson; Bertrand Kuhnast; Magnus Schou; et al. (MDPI AG, 2022)
Crizotinib is a tyrosine kinase inhibitor approved for the treatment of non-small-cell lung cancer, but it is inefficient on brain metastases. Crizotinib is a substrate of the P-glycoprotein, and non-invasive nuclear imaging can be used to assess the brain penetration of crizotinib. Positron emission tomography (PET) imaging using fluorine-18-labeled crizotinib would be a powerful tool for investigating new strategies to enhance the brain distribution of crizotinib. We have synthesized a spirocyclic hypervalent iodine precursor for the isotopic labeling of crizotinib in a 2.4% yield. Because crizotinib is an enantiomerically pure drug, a chiral separation was performed to afford the (R)-precursor. A two-step radiolabeling process was optimized and automated using the racemic precursor to afford [18F](R,S)-crizotinib in 15 ± 2 radiochemical yield and 103 ± 18 GBq/µmol molar activity. The same radiolabeling process was applied to the (R)-precursor to afford [18F](R)-crizotinib with comparable results. As a proof-of-concept, PET was realized in a single non-human primate to demonstrate the feasibility of [18F](R)-crizotinib in in vivo imaging. Whole-body PET highlighted the elimination routes of crizotinib with negligible penetration in the brain (SUVmean = 0.1). This proof-of-concept paves the way for further studies using [18F](R)-crizotinib to enhance its brain penetration depending on the P-glycoprotein function.